MIXED SCHOOL ABILITIES DISORDERS - Boni, Cinara; Larissa da Silva Flores, Juliane; Piccoli Diehl, Rosicler; Possa Moreschi, Margarida; Zancan, Sinara; Raquel Faccin, Tânia; Scalcon dos Santos de Lima, Marta (Revista Gênero e Interdisciplinaridade, 2023)
The mixed school ability disorder is based on the diagnosis and intervention of the child with learning difficulties, the earlier the diagnosis, the sooner the treatment begins and the better the school performance. The ludic enables experiences to occur, creative when practiced seriously, one can obtain through games a moment of discovery of oneself and the other. Carry out mechanisms aimed at carrying out activities capable of adding to the student’s learning difficulties, improving the self-esteem of the child with learning difficulties through playful, constructive activities based on the child’s reality, so that he has the desire to learn and so their degree of disability is overcome. Social factors are also determinant in learning problems, and among them is the school and family environment, they are the main components of these factors. According to (PAIN 1985, p.130). Learning difficulties would be related to causes external to the family and individual structure, originating the reactive learning problem, in which it affects learning but does not imprison intelligence and, generally arises from the confrontation between the student and the institution; Internal causes the family and individual structure the problem is considered as a symptom and inhibition, affecting the dynamics of necessary articulations between organism, body, intelligence and desire, causing the unconscious desire not to know and therefore not to learn. As for the school environment, it is necessary to verify the motivation and training of the teaching team, the quality of the relationship between teacher and student, family, the pedagogical proposal, and the level of demand of the school, which is often concerned only with competitiveness. and puts aside the creativity of his students. In relation to the family with a high sociocultural level, it can deny the existence of school difficulties of the child. There are also cases in which the family presents a very high level of demand with a view focused on the results obtained, which may develop in the child a degree of anxiety that does not allow the child to have an adequate learning process. It is essential that school and family walk together for the best development of these children, developing their knowledge with great love.